Islamic communication strategies of mediators at the Mahkamah Syar’iyah in mediating divorce cases - Saidaturrahmah; Lubis, Lahmuddin; Nasution, Syawaluddin (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
This study aims to analyze the implementation of Islamic communication strategies by mediators at the Mahkamah Syar’iyah (Sharia Court) of Bireuen Regency, Indonesia, in mediating divorce petition cases. The background of this research lies in the high number of divorce cases filed annually, while the mediation success rate remains relatively low. The study employs a qualitative approach through field research. Data were collected via in-depth interviews with the Chief Judge of the Mahkamah Syar’iyah and mediator judges, supported by the examination of official court documents. The findings reveal that although Islamic communication principles, such as hikmah (wisdom), mau’izhah hasanah (good counsel), and mujadalah billati hiya ahsan (best form of debate), have been incorporated into the mediation process, their implementation still faces significant challenges, including limited human resources, the absence of specific Standard Operating Procedures (SOPs), and the diverse socio-cultural backgrounds of the parties involved. Nevertheless, Islamic communication strategies have proven effective in fostering constructive dialogue, promoting mutual respect, and offering fair solutions aligned with Islamic law. The study recommends enhancing mediator capacity, strengthening technical regulations, and developing standardized procedures to improve mediation success rates in the future. ***** Penelitian ini bertujuan untuk menganalisis strategi komunikasi Islami yang diterapkan oleh mediator di Mahkamah Syar’iyah Kabupaten Bireuen, Indonesia, dalam memediasi pasangan yang mengajukan gugat cerai. Latar belakang penelitian ini adalah tingginya jumlah perkara perceraian yang masuk setiap tahun, sementara tingkat keberhasilan mediasi relatif rendah. Pendekatan penelitian yang digunakan adalah kualitatif dengan metode penelitian lapangan (field research). Data diperoleh melalui wawancara mendalam dengan Ketua Mahkamah Syar’iyah dan para hakim mediator, serta didukung oleh telaah dokumen resmi pengadilan. Hasil penelitian menunjukkan bahwa meskipun prinsip-prinsip komunikasi Islami seperti hikmah, mau’izhah hasanah, dan mujadalah billati hiya ahsan telah diupayakan untuk diimplementasikan, pelaksanaannya masih menghadapi berbagai hambatan, termasuk keterbatasan sumber daya manusia, belum adanya SOP khusus, serta perbedaan latar belakang sosial-budaya para pihak. Namun demikian, strategi komunikasi Islami terbukti berkontribusi dalam membangun dialog yang konstruktif, menumbuhkan rasa saling menghormati, serta memberikan alternatif solusi yang lebih berkeadilan dan sesuai syariat. Penelitian ini merekomendasikan peningkatan kapasitas mediator, penguatan regulasi teknis, dan pengembangan prosedur baku guna mengoptimalkan keberhasilan mediasi di masa mendatang.